Granulocytes harvested following G-CSF-enhanced leukocyte recovery retain their functional capacity during in vitro culture for 72 hours - Martin, Simona; Frühauf, Stefan; Zeller, W. Jens; Haas, Rainer (Journal of hematotherapy, 1996)
The purpose of this study was to compare two different in vitro culture conditions for the preservation of human granulocytes. These cells could be used in patients with severe neutropenia following cytotoxic chemotherapy if the functional capacity was retained, and autologous transfusions of granulocytes would circumvent the risk of alloimmunization. Granulocytes were obtained from the peripheral blood of healthy donors and patients with hematologic malignancies who received cytotoxic chemotherapy supported by recombinant human granulocyte colony-stimulating factor (R-metHuG-CSF, 300 μg/day, s.c). Granulocytes were either cultured for 72 h at 4°C in the presence of 100 ng/ml G-CSF or cryopreserved at −196°C. The viability, surface antigen expression, and function of the granulocytes were assessed. Since effective microbial killing involves the attachment of granulocytes to blood vessel walls, transmigration into tissues, chemotaxis, and phagocytosis, the surface expression of the adhesion molecules LFA-1 (CD11a/CD18) and gp 150,95 (CD11c/CD18) was measured. In addition, the IgG receptors FcγRI (CD64), FcγRII (CD32), and FcγRIII (CD16), as well as the complement receptor CR3 (CD11b/CD18), were assessed. Dynamic Superoxide anion release served as a measure of the metabolic pathway of the oxidative burst after f-Met-Leu-Phe (fMLP) and phorbol-12-myristate-13-acetate (PMA) stimulation. Substantial differences in the preservation of granulocyte integrity and function were observed between the two storage conditions. Cryopreservation abolished reactivity to extracellular stimuli and severely affected the cell phenotype. On the other hand, functional activity could be maintained for up to 72 h when in vivo primed granulocytes of patients were incubated at 4°C in the presence of G-CSF. This storage modality may permit the use of granulocyte autotransfusion to reduce the risk of neutropenic fever.
Elektronische Reproduktion der Druck-Ausgabe 27. März 2009
Gesehen am 15.05.2025